Pengaruh Transformasi Digital, Capital Intensity, Kepemilikan Institusional dan Umur Perusahaan terhadap Tax Avoidance: (Studi Empiris pada Perusahaan Subsektor Industri Makanan dan Minuman di Bei Tahun 2020 - 2024) - Shafa Tarisa Ananda,; Anissa Amalia Mulya, (AKUNTANSI 45, 2026)
This study aims to analyze the effect of digital transformation, capital intensity, institutional ownership, and firm age on tax avoidance. The research object consists of food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique used is purposive sampling, resulting in 31 companies with a total of 155 observations. This study employs secondary data obtained from companies’ annual financial statements. The data were analyzed using multiple linear regression with the assistance of the Statistical Product and Service Solution (SPSS) program. The results indicate that digital transformation has a significant effect on tax avoidance, while capital intensity, institutional ownership, and firm age do not have a significant effect on tax avoidance.